ANALISIS KEPUASAN PELANGGAN DENGAN DIMENSI KUALITAS PELAYANAN MENGGUNAKAN METODE SERVQUAL CSI DAN KAIZEN DI KOPERASI SYARIAH XYZ - Muhammad Irham Taufik (Journal of Management and Industrial Engineering (JMIE), 2024)
Sharia financial services have recently become a sector that is quite popular with the public because they can be an alternative for carrying out mu'amalah transactions in a shari'ah manner. XYZ Cooperative is one of the sharia financial services in the city of Bandung. However, data from the last 12 months shows that the graph of members leaving the XYZ cooperative continues to increase, which is thought to be due to the quality of service and miscommunication between members' perceptions and the institution's policies. This research aims to determine customer satisfaction based on service quality dimensions and determine priority attributes that must be improved in the XYZ cooperative to enhance the quality of service. The sample for this research was 90 respondents. The methods used are the SERVQUAL and CSI methods to determine the level of satisfaction of members of the XYZ cooperative and determine the priority attributes that must be improved, followed by the kaizen method as a proposal for improvement by applying PDCA. Data collection was carried out using a questionnaire and processed with the help of IBM SPSS Statistics software. The results of this research show the overall satisfaction of members of cooperatives using the kaizen method.